Pengaruh Kontaminan Air terhadap Tegangan Tembus Isolasi Cair Minyak Mineral dan Nabati sebagai Alternatif Isolasi Minyak Transformator - Christiono; Miftahul Fikri; Dhami Johar Damiri; Muh. Rezha Safariansyah; Syahty Pratiwi; M. Reza Hidayat (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
One of the effects of reduced transformer life is the frequent occurrence of disturbances, disturbances that can occur in the form of contamination of insulating oil which has an impact on transformer damage. To reduce the damage, a research was carried out, in this study it was carried out to see the effect of water contaminants contained in the insulation of transformer oil using the Breakdown Voltage method by looking at the value of the translucent voltage. There are 2 types of insulating oil used during testing, mineral, and vegetable oil, while the test equipment used is the BAUR Oil Tester DPA, with the standard IEC 60156:2018 test equipment. Which is adapted to the standard specification SPLN 49-1:1982 which states that new oil has a breakdown voltage value of 30 kV/2.5 mm. The results of the test show that the breakdown voltage value is influenced by water contaminants where the more contaminants contained, the faster the breakdown voltage value will decrease. This research can be an indication to maintain the transformer resistance.